Bioregulators of stem and progenitor cells in preservation solution reduce cold ischemia-reperfusion injury of isolated rat livers - Cherkashina, Daria; Sosimchyk, Irina; Semenchenko, Olga; Semenchenko, Alexander; Volina, Victoria; Petrenko, Alexander (Wiley, 2016)
The effects of bioregulators of stem and progenitor cells (BSPC) of fetal tissue cytosol on rat liver during 24h hypothermic storage (HS) and following normothermic reperfusion (NR) were investigated. It was shown that BSPC presence in the preservation medium stabilized pro-oxidant-antioxidant balance impaired in liver after HS and NR, prevented the uncoupling of mitochondrial oxidative phosphorylation and ATP level decline. These consequences led to significant improvement of hepatic morphological integrity and functional state. Powerful protective effect of BSPC on liver at sub-zero temperatures can serve as basis for new approaches to extend safe time for organ preservation and foster understanding of pathways of stem and progenitor cell paracrine action
Keywords: bioregulators; ischemia-reperfusion; liver hypothermic storage; preservation solution; stem and progenitor cells